Development of Student Worksheets (LKPD) Based on Problem Based Learning to Improve Learning Outcomes in Business Economics Subjects - Monika Karolina Sianturi; Arwansyah Arwansyah; Muhammad Yusuf (EDUTEC : Journal of Education And Technology, 2021)
The curriculum in Indonesia is currently curriculum 2013, especially on the basic framework and structure of the vocational curriculum that states that the 2013 curriculum was developed with the improvement of mindset, among others: educationthat focuses on teachers so focused on students, as well as passive learning so active learning. Therefore, as a teacher can develop the learning process, especially learning resources that are able to explore the ideas of students into an innovative and critical so that they can produce and solve theirown problems,through problem-based LKPD learning. This method and type of research is a development study with a 4-Dmodelby Thiagarajan and Semmel. The findings in this study are the use of problem-based learning-based LKPD and the response of students who were found to be positive or good